Proposta de índice de qualidade da água flexível e integrado à legislação: uma análise de dados oficiais em pontos de captação de água - Récio, Larissa Vareschi (2021)
Agroindustrial development and urbanization associated with growing deforestation rates have affected the volume and quality of surface water, which is why the management of water resources is of paramount importance for its preservation. In this scenario, analysis and monitoring methods and tools must be adopted in order to estimate the environmental situation of water bodies from the interpretation of water quality data. In Brazil, the method used and accepted for this assessment is the Water Quality Index IQA, which results from a weighted product of nine fixed parameters. However, the assessment obtained by the IQA has limitations that need to be considered. Thus, the general objective of this study was to propose a new water quality index that considers the inclusion and exclusion of variables, is integrated with current legislation and includes a graphic resolution that is easy to interpret. Thus, the Water Quality NonConformity Index IDQA was proposed, which was adapted from the Integrated Response Biomarkers Index IBR, and applied to an existing official database. Five Water Treatment Plants (ETAs) in the state of Paraná were selected and the nine IQA parameters were obtained during the period 2018 to 2019, including those of the ETA Campo Mourão (ETACM). The reference values were defined based on CONAMA Resolution nº 357/2005 for classes 1 and 2. The results obtained for the IDQA were compared to the IQACETESB and IQANSF. In order to demonstrate the flexibility of the IDQA, the new index was also located from the database of the work carried out by Ghisi et al. (2017), entitled "Multivariate and integrative approach to analyzing multiple biomarkers in ecotoxicology: A field study in the Neotropical region", in which nonconventional variables were analyzed to infer about water quality, such as aluminum, copper and zinc , at points ETACM and ETECM of Rio do Campo, with reference to CONAMA nº 357/2005. Still, a second analysis complemented by biological data was carried out, using data from the Perobas Biological Reserve (REBio) as a reference. In general, the IQAs show noncompliance with five ETAs with high levels of Escherichia coli followed by total phosphorus and sometimes turbidity, classifying the sites as altered or alert, while the IQAs from acceptable to good. From the second database, the IDQA highlighted noncompliance in Rio do Campo, classifying the points as polluted or qualified. All metals were above what is allowed in the legislation and the biological indicators showed toxicological risk. The new index proves to be a promising, flexible tool, adjusted to legislation, which does not omit variables in disagreement and regional issues.